Corrosion Products Electrochemical Behaviour into Molten LiF-NaF: Investigation of Cr(II) System. Issue 2 (5th February 2021) - Massot, L.; Gibilaro, M.; Quaranta, D.; Chamelot, P.
Abstract : In this work, a detailed electrochemical study of the molten LiF-NaF-CrF2 system is provided on Ag electrode in the 750 °C–900 °C temperature range. The first part was dedicated to the electrochemical study, by cyclic and square wave voltammetries, allowing the determination of thermodynamic and physico-chemical data such as CrF2 /Cr standard potential, diffusion coefficient, activity coefficient, transfer energy and nucleation overvoltage. The influence of Li2 O addition on the electrochemical reduction pathway of dissolved CrF2 on a silver electrode was investigated. The results showed that an increase of Li2 O activity in the solution causes CrF2 disproportionation into solid chromium oxide and metallic Cr.